Successful Implementation Model of Risk Management and Risk Based Internal Audit in Era Digital: A Systematic Literature Review - Harahap, Angginun Juwita Sari; Muda, Iskandar (Westscience Press, 2025)
The advancement of digitization creates additional chances for the effective execution of risk management and risk-based internal auditing inside an agency. This research seeks to examine the practice of risk management and risk-based internal auditing in the public sector, analyze the implementation model of these practices, and identify the successful models for their execution. The preliminary study involved the analysis of information about risk management and risk-based internal audits sourced from the Scopus Database, published between 2021 and 2024. This study was executed utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. This study identified five domains of risk management and risk-based internal audit outcomes in the era of digitalization, specifically (1) Internal audit, (2) Risk Management, (3) Influencial factors, (4) Audit committee, (5) Integrity system and (6) transformational technology. This research also found areas that need attention for future research, namely artificial intelligence which is part of the current development of digitalization.